2019
DOI: 10.1016/j.neulet.2018.10.042
|View full text |Cite
|
Sign up to set email alerts
|

The role of TRP channels in white matter function and ischaemia

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 111 publications
(148 reference statements)
0
11
0
Order By: Relevance
“…Similarly, Ca 2+ extrusion through PMCA has been shown to decrease in aged neurons (Jiang et al, 2012). For this reason, these NDs are associated with Ca 2+ channels in neurons and glial cells (astrocytes, microglia, and oligodendrocytes), which are important for neuronal survival, myelin formation, neuronal support, and regulation of local neuron activity (neurons-glial signaling) (Zhang and Liao, 2015;Cornillot et al, 2019;Enders et al, 2020). Riccio et al, 2002;Bollimuntha et al, 2005Bollimuntha et al, , 2006Selvaraj et al, 2009Selvaraj et al, , 2012Hong et al, 2015…”
Section: Brain Disorders Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ca 2+ extrusion through PMCA has been shown to decrease in aged neurons (Jiang et al, 2012). For this reason, these NDs are associated with Ca 2+ channels in neurons and glial cells (astrocytes, microglia, and oligodendrocytes), which are important for neuronal survival, myelin formation, neuronal support, and regulation of local neuron activity (neurons-glial signaling) (Zhang and Liao, 2015;Cornillot et al, 2019;Enders et al, 2020). Riccio et al, 2002;Bollimuntha et al, 2005Bollimuntha et al, , 2006Selvaraj et al, 2009Selvaraj et al, , 2012Hong et al, 2015…”
Section: Brain Disorders Neurodegenerative Diseasesmentioning
confidence: 99%
“…Based on functional characterization of TRP channels by a wide range of stimuli (Zheng, 2013), aberrant activity of TRP channels likely initiates and/or propagates ND processes, especially cell death, via increased intracellular Ca 2+ in various brain regions (Moran, 2018;Hong et al, 2020;Huang et al, 2020). Here, we focus on the function of TRP channels associated with Ca 2+ signaling in neurons and glial cells (Figure 1A) (Nilius, 2007;Bollimuntha et al, 2011;Zheng, 2013;Zhang and Liao, 2015;Jardin et al, 2017;Sawamura et al, 2017;Hasan and Zhang, 2018;Samanta et al, 2018;Cornillot et al, 2019;Enders et al, 2020;Wang et al, 2020). Based on sequence homology, the TRP family currently comprises 28 mammalian channels and is subdivided into six subfamilies: TRP canonical (TRPC), TRP vanilloid (TRPV), TRP ankyrin (TRPA), TRP melastatin (TRPM), TRP polycystin (TRPP), and TRP mucolipin (TRPML) (Nilius, 2007;Selvaraj et al, 2010;Nishida et al, 2015;Sawamura et al, 2017).…”
Section: Pathophysiological Role Of Trp Channelsmentioning
confidence: 99%
“…These features and the wide expression of these channels in multiple tissues and cell types, grant a high level of complexity to their role in diverse physiological and pathophysiological processes ( Venkatachalam and Montell, 2007 ). In this context, several TRP channels are implicated in cellular processes related to central nervous system (CNS) functioning such as the modulation of neuronal excitability ( Mickle et al, 2016 ; Hong et al, 2020b ), maturation or establishment of subcellular structures such as dendrites ( Tai et al, 2008 ), excitatory synapses ( Zhou et al, 2008 ), axonal outgrowth ( Jang et al, 2014 ), frontal cortex postnatal development ( Riquelme et al, 2018 ) and brain blood flow regulation ( Earley et al, 2004 ; Cornillot et al, 2019 ). Also, current evidence suggests that TRP channels could regulate downstream processes such as gene expression or more lasting effects, like Long Term Potentiation (LTP).…”
Section: Trp Channelsmentioning
confidence: 99%
“…Ion channels have been widely described as pivotal molecular entities that contribute to brain physiology and are associated to the development of various brain diseases, thus emerging as highly potential pharmacological targets ( Bagal et al, 2013 ). Several members of the TRP ion channel family play key roles in the regulation of cellular and tissue structures, such as membrane protrusions, synapses, endothelial barriers and glial architecture ( Goswami and Hucho, 2007 ; Goswami et al, 2007a ; Gorse et al, 2018 ; Zhao et al, 2018 ; Cornillot et al, 2019 ), whose abnormal activity is intimately linked to neurodevelopmental and neurodegenerative disorders ( Morelli et al, 2013 ). Despite that, how TRP channels participate in brain physiology and brain-affecting diseases is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…TRPA1 is one of a large family of tetrameric non-selective cation channels that are widely expressed in the grey and white matter of the CNS and are increasingly considered as potential therapeutic targets in brain disorders (Cornillot et al, 2019). TRPA1 is sensitive to environmental irritants and endogenous electrophilic compounds that are formed during oxidative stress (Andersson et al, 2008), which have been shown to evoke pain, cold, itch and inflammation (Bautista et al, 2013).…”
Section: Introductionmentioning
confidence: 99%